Comparing the apical microleakage of lateral condensation and chloroform dip techniques with a new obturation method - Masoud Saatchi; Behnaz Barekatain; Masoumeh Behzadian (Wolters Kluwer Medknow Publications, 2011)
Background: The final objective of root canal therapy is to create a hermetic seal along the length of the root canal system. For this purpose, many methods and materials have been introduced. The purpose of this study was to compare the apical microleakage in a new obturation technique (true-tug-back) with two other obturation techniques (lateral condensation and chloroform dip technique). Methods: In this in vitro study 102 single canal teeth were selected. The crowns were removed, and the canals were prepared using step-back technique. The master apical file was K-file #40. The teeth were divided into 3 experimental groups of 32 teeth. First group were obturated with lateral condensation technique and second group with chloroform dip technique and the third group with true-tug-back technique. Six teeth were used as control group. The teeth were placed in incubator at 100% humidity and 37°c for three days. The roots of the teeth were coated with two layers of nail varnish except for the apical 2 millimeter. Teeth were placed in Methylene blue 2% for one week. The teeth were sectioned vertically and the depth of maximum dye penetration for each tooth was recorded by stereomicroscope. Data were analyzed using ANOVA and Dunkan test. Results: The mean liner dye penetration differences between lateral condensation group (6.88 ± 4.06 mm) and chloroform dip technique group (7.16 ± 3.37 mm) were not statistically significant (P = 0.719). The differences between true-tug-back group (3.15 ± 0.52 mm) and two other groups were statistically significant (P < 0.001). Conclusion: The results of this study showed that the true-tug-back technique can improve apical seal. Further studies are needed for this purpose.